Statistical Control of Time Standards - Langier, Franciszek Jan (Management Science, 1963)
An application of the statistical control of time standards developed by the author has, quite unexpectedly, created the possibility of a further application of this method as an indicator of organisational deficiencies in industry which, at the same time, makes it possible to locate these deficiencies in the respective plants, departments and workshops.